PERAN PENILAIAN ETIS PADA PENGARUH RELIGIUSITAS TERHADAP PERILAKU PEMBELIAN RAMAH LINGKUNGAN - Purbo Jadmiko (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2018)
Applying the conceptual framework of value-attitude-behavior relationship, the present study investigates the role of ethical judgment as mediating effect religiosity to green purchase behavior. Using linier regression analysis, the role of ethical judgment, religiosity on green purchase behavior are investigated. The subject of the research is costumer in Padang. Results suggest that religiosity positive significant to green purchase behavior. But, ethical judgment has partial mediated between religiosity on green purchase behavior. Implications and directions for future research are discussed.